Korelasi Tanggung Jawab dan Motivasi Belajar dengan Prestasi Belajar Matematika Siswa Kelas V SD - Nurika Anggraini; Fery Muhamad Firdaus (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The study aims to determine the correlation between: 1) responsibility and mathematics learning achievement of 5th grade students, 2) motivation and mathematics learning achievement of 5th grade students, and 3) responsibility and motivation and the mathematics learning achievement of 5th grade students. This research was correlational with population was 225 and sample totaled 144 students. The sampling technique used was stratified sampling followed by simple random. The research instrument was in the form of a questionnaire and documentation of report card scores. Data analysis used was simple regression analysis, multiple regression analysis, coefficient of determination and variable contribution. The results of this study indicate a correlation between: (1) responsibility and mathematics learning achievement as evidenced by a significance value of 0.014 < 0.05, an R-squared value of 0.042, and a positive regression coefficient (β) of 0.137, indicating a positive influence of 4.2%; (2) learning motivation and students’ mathematics learning achievement, supported by a significance value of 0.041 < 0.05, an R-squared value of 0.029, and a positive regression coefficient (β) of 0.102, indicating a positive influence of 2.9%; and (3) the simultaneous effect of responsibility and learning motivation on mathematics learning achievement, as shown by a significance value of 0.048 < 0.05, a combined R-squared value of 0.042, and positive regression coefficients of 0.130 for responsibility and 0.008 for motivation, indicating a total positive contribution of 4.2%.